Role of Dust Grains in Beam-Driven Instabilities. (2018) - Sharma, S.C.; VedPrakash; Gupta, Ruby
Abstract: The interaction of beam with magnetized plasma can lead to the excitation of many instabilities which are useful for understanding the stability, confinement and heating of the plasma. In the present work, we investigate the electromagnetic surface plasma waves, lower hybrid waves and ion cyclotron waves in three component dusty plasmas. The presence of charged dust grains modifies the dispersion relation of plasma waves. The charge and number density of dust grains and external magnetic field significantly modify the dispersion properties of these waves. It is shown that in the absence of beam, the plasma mode damps due to dust charge fluctuations and an additional damping dust charge fluctuation mode is induced in plasma. The beam propagating parallel or perpendicular to the magnetic field drives the plasma waves to instability via Cerenkov and cyclotron interaction. Using the analytical and numerical results the influence of the number density of negatively charged dust grains on growth rate of instabilities is studied.